PERSPECTIVES ON DEVELOPING E-LEARNING AT THE STATE BORDER GUARD COLLEGE OF THE REPUBLIC OF LATVIA - Spridzāns, Mārtiņš; Pavlovičs, Jans (Border Security and Management, 2016)
The authors of this article describe the development process of e-learning system at the State Border Guard College, depict theoretical and practical concepts, peculiarities of e-course’s development. Suggestions and proposals on e-course development and improvement based on the experience gained during e-learning course development and administration supported by survey results are given in the conclusion of this article in order to facilitate the improvement of e-learning systems in other law enforcement agencies.